Brain age gap, dementia risk factors and cognition in middle age - Stefaniak, JD; Mak, E; Su, L; Carter, SF; Dounavi, M; Muniz Terrera, G; Bridgeman, K; Ritchie, K; Lawlor, B; Naci, L; Koychev, I; Malhotra, P; et al. (Oxford University Press, 2024)
Brain Age Gap has been associated with dementia in old age. Less is known relating brain age gap to dementia risk-factors or cognitive performance in middle-age. Cognitively healthy, middle-aged subjects from PREVENT-Dementia had comprehensive neuropsychological, neuroimaging and genetic assessments. Brain Ages were predicted from T1-weighted 3T MRI scans. Cognition was assessed using the COGNITO computerized test battery. 552 middle-aged participants (median [interquartile range] age 52.8 [8.7] years, 60.0% female) had baseline data, of whom 95 had amyloid PET data. Brain age gap in middle-age was associated with hypertension (P = 0.007) and alcohol intake (P = 0.008) but not apolipoprotein E epsilon 4 allele (P = 0.14), amyloid centiloids (P = 0.39) or cognitive performance (P = 0.74). Brain age gap in middle-age is associated with modifiable dementia risk-factors, but not with genetic risk for Alzheimer's disease, amyloid deposition or cognitive performance. These results are important for understanding brain-age in middle-aged populations, which might be optimally targeted by future dementia-preventing therapies.